Strategies for Optimizing Growth in Children With Chronic Kidney Disease - Dieter Haffner (Frontiers Media S.A., 2020)
Growth failure is a hallmark in children with chronic kidney disease (CKD). Therefore, early diagnosis and adequate management of growth failure is of utmost importance in these patients. The risk of severe growth retardation is the higher the younger the child is, which places an additional burden on patients and their families and hampers the psychosocial integration of these children. Careful monitoring of growth, and effective interventions are mandatory to prevent and treat growth failure in children with CKD at all ages and all stages of kidney failure. Early intervention is critical, as all therapeutic interventions are much more effective if they are started prior to the initiation of dialysis. Prevention and treatment of growth failure focuses on: (i) preservation of renal function, e.g., normalization of blood pressure and proteinuria by use of inhibitors of the renin-angiotensin aldosterone system, (ii) adequate energy intake, including tube feeding or gastrostomy in case of persisting malnutrition, (iii) substitution of water and electrolytes, especially in children with renal malformation, (iv) correction of metabolic acidosis, (v) control of parathyroid hormone levels within the CKD-dependent target range, (vi) use of recombinant human growth hormone in cases of persistent growth failure, and, (vii) early/preemptive kidney transplantation using steroid-minimizing immunosuppressive protocols in children with end-stage CKD. This review discusses these measures based on recent guidelines.